2022
DOI: 10.1155/2022/4624311
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Complementary and Alternative Medicine on Female Infertility Caused by Endometrial Factors

Abstract: Recently, with the development of the social economy, the incidence of infertility has increased year by year. With its complex etiology and diversified syndromes, infertility has become one of the most important diseases that plague the physical and mental health of women of childbearing age worldwide. Endometrial factors as an important part affecting female reproductive capacity, due to which induced repeated abortion and multiple uterine cavity operations occur, can destruct endometrium, failing to provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 122 publications
0
2
0
Order By: Relevance
“…EGF stimulates the growth of glandular cells in the proliferative and secretory endometrium and facilitates the epithelial-mesenchymal transition (Okada et al, 2022). CSF stimulates cell proliferation, which has no change in the menstrual cycle, but its concentration increases significantly in early pregnancy (Lin et al, 2022). In our study, based on our sequencing analysis, we screened two of the most upregulated lncRNAs in the RE tissue and explored their roles in primary goat endometrial epithelial cells through adenovirus-mediated overexpression experiments.…”
Section: Discussionmentioning
confidence: 99%
“…EGF stimulates the growth of glandular cells in the proliferative and secretory endometrium and facilitates the epithelial-mesenchymal transition (Okada et al, 2022). CSF stimulates cell proliferation, which has no change in the menstrual cycle, but its concentration increases significantly in early pregnancy (Lin et al, 2022). In our study, based on our sequencing analysis, we screened two of the most upregulated lncRNAs in the RE tissue and explored their roles in primary goat endometrial epithelial cells through adenovirus-mediated overexpression experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The compound is clinically used for the treatment of infertility, polycystic ovary syndrome, thin endometrium, repeated implant failure, and premature ovarian insufficiency. [6][7][8] While clinical studies to date have confirmed that YJZYT increases endometrial thickness, improves endometrial receptivity, and augments the clinical pregnancy rate, its specific mechanisms of action are yet to be established. 9,10 Despite considerable research, the pharmacological interpretation of TCM prescriptions still faces significant challenges, which greatly hinders the widespread clinical application of TCM worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…They may be uninsured in some circumstances and countries [6]. Therefore, many patients utilize complementary medicine to improve the efficacy of their treatment and minimize potential side effects [7]. For example, data from Turkey and Iran reveal that around half of infertile patients have used complementary medicine methods.…”
mentioning
confidence: 99%